Diagnóstico socioambiental da coleta seletiva no município de Campo Mourão - PR - Bortolon, Diego Rodrigo (2014)
The present course conclusion work aimed to make a diagnosis socioenvironmental of selective collection in the city of Campo Mourão – PR. Thus, visits were made and semi-structured interviews with the agents involved in selective collection municipal, the Secretariat of the Environment, the company holder of public services of urban cleaning and solid waste management and organizations formalized by collectors of recyclable materials. The visits to the undertaking of collection services and organizations of waste pickers had the purpose to identify the infrastructure of organizations and raise information cuali-quantitative that subsidized the survey. The results showed that the municipality has an association and a cooperative in operation, on average the selective collection gathering 70 tons per month of recyclable materials which represent only 3.5% of total generation of Urban Solid Residues. The company responsible for the collection draws up an annual Plan of Environmental Education that provides for partnerships with the municipal executive and with private entities in activities to different local organizations and state and municipal schools. It is concluded from the diagnosis that the Municipal Public Power performs discrete actions of environmental education, those in partnership with the company holder of collection services, and supervision regarding the participation of the population in selective collection system is non-existent. The wastepicker organization needs improvements in infrastructure and support of the municipality. The main impediment to progress in administration and management of selective collection is the inexistence of a Municipal Plan for Integrated Management of Solid Wastes that set goals and specific programs aimed at the promotion of the system.